Fertilizante orgânico composto e água residuária no desenvolvimento de trigo irrigado por gotejamento - Kummer, Ana Carolina Barbosa; Grassi Filho, Helio [UNESP]; Lobo, Thomaz Figueiredo; Lima, Rodollpho Artur De Souza (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2017)
The objective of this study was to evaluate the effect of organic compound fertilizer use (composted sewage sludge - CSS) in wheat plants irrigated with wastewater from the output of a sewage treatment plant. Completely randomized design was used in a split plot, adopting in the plots two types of water for irrigation (drinking water - DA and wastewater - WW) and in subplots seven nitrogen fertilization levels, described as follows: T1 without nitrogen fertilization; T2, 80 kg ha-1 of N of urea; T3, 40 kg ha-1 N of urea + 40 kg ha-1 N of CSS; T4, T5, T6 and T7 corresponded to 80, 120, 160 and 200 kg ha-1 N of CSS, respectively. Irrigation with WW promoted increments of 36, 100, 48 e 77% of dry matter (DM), number of tillers (NT), number of spikes per plant (NS) and grain yield per plant (GY), respectively. The use of wastewater with doses of nitrogen above 80 kg ha-1 from composed sewage sludge, promoted decreases in spike length, dry mass and grain yield. The results point to the substitution of 100% of the chemical nitrogen fertilization (dose of 80 ka ha-1 of N), by the equivalent in N from CSS (100% sludge), without damages to the wheat crop.
Organic compound fertilzer and wastewater in the development of wheat irrigated by dripping
Keywords: Compound; Irrigation; Nitrogen; Sludge; Wastewater